2020
DOI: 10.1007/698_2019_442
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Toxicological Effects of UV-Filters on Marine Species

Abstract: UV-filters are of emerging concern and their toxicity have been demonstrated in many papers. Organic and mineral UV-filters are active ingredients found in sunscreens. Due to the presence of UV-filters in marine waters, studies on these compounds bioaccumulating in organisms have been carried out and this has been complemented by toxicity studies, with reports of detrimental effects to a variety of organisms. This chapter gives an overview of the bioaccumulation and the toxicity of sunscreen UVfilters on marin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 145 publications
2
37
0
Order By: Relevance
“…Also, it has been demonstrated that BP3 can be absorbed through the skin but the effects of elevated systemic BP3 concentrations in humans are still unclear (Suh et al, 2020). BP3 has been shown to be toxic in several species used for toxicological testing including fish, corals and algae (see recent review and references therein (Lozano et al, 2020)). Thus, the toxicity of BP3 combined with the possibility of bioaccumulation indicates that BP3 might pose an ecological risk (Díaz-Cruz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been demonstrated that BP3 can be absorbed through the skin but the effects of elevated systemic BP3 concentrations in humans are still unclear (Suh et al, 2020). BP3 has been shown to be toxic in several species used for toxicological testing including fish, corals and algae (see recent review and references therein (Lozano et al, 2020)). Thus, the toxicity of BP3 combined with the possibility of bioaccumulation indicates that BP3 might pose an ecological risk (Díaz-Cruz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…behavior [15,16], growth [14,17,18], development [19,20], metabolism [21][22][23], gene expression [24,25] and reproduction [15,26,27] in various species. It should be noted that most toxicological studies on organic UV filters were conducted on BP3, EMC and 4-MBC [7]. BP3 and EMC have been banned in Hawaii and Key West, Florida The Republic of Palau and U.S Virgin Islands have also banned these two UV-filters, as well as OC.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, 60 different UV filters were reported on the market; these compounds are subject to different regulations around the world [ 4 ]. UV filters are regularly detected in various aquatic environmental compartments, including lakes, rivers, surface marine waters and sediments [ 3 , 5 , 6 , 7 ]. Some UV filters have been investigated more than others in occurrence studies, such as benzophenone-3 (BP3), ethylhexyl methoxycinnamate (EMC), octocrylene (OC) and 4-methylbenzylidene camphor (4-MBC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing tourism results in their direct and indirect discharge in aquatic biota, through bathing and wastewater treatment plants 1 . Their occurrence was reported in freshwater and marine environments from the surface microlayer 2 , water column 3,4 to sediments [5][6][7] , along with their bioaccumulation and biomagni cation properties 8 . UV lters toxicity was demonstrated on a broad range of organisms [9][10][11][12][13][14][15] , including bacteria 16 , yet UV lters toxicity mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%